Pelagios – Connecting Histories of Place. Part II: From Community to Association. Issue 1 (October 2021) - Kahn, Rebecca; Isaksen, Leif; Barker, Elton; Simon, Rainer; de Soto, Pau; Vitale, Valeria
Abstract : This article, which forms the second part of a two-part article in this volume, reflects on what we argue to be the most crucial element of any Linked Data enterprise: its community. The first section discusses a variety of funded and unfunded activities conducted under the aegis of Pelagios, and specifically two 'small grant' programmes that dramatically expanded its scope and reach. The second section describes the evolution of Pelagios as a 'community of practice', in which the work of the initiative, conceived of in terms of both method and tool development, has been facilitated by, and coordinated with, individuals and groups external to its investigative teams. This growing and maturing community has ultimately been realized in the foundation of a formal voluntary organization: the Pelagios Network Association. The paper concludes with brief reflections on some interlinked sister initiatives that have emerged from the Pelagios community and continue to support scholars and practitioners working in related fields.